2001
DOI: 10.1128/jcm.39.10.3486-3490.2001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Malassezia Microflora on the Skin of Atopic Dermatitis Patients and Healthy Subjects

Abstract: Members of the genus Malassezia, lipophilic yeasts, are considered to be one of the exacerbating factors in atopic dermatitis (AD). We examined variation in cutaneous colonization by Malassezia species in AD patients and compared it with variation in healthy subjects. Samples were collected by applying transparent dressings to the skin lesions of AD patients. DNA was extracted directly from the dressings and amplified in a specific nested PCR assay. Malassezia-specific DNA was detected in all samples obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(111 citation statements)
references
References 25 publications
2
107
1
1
Order By: Relevance
“…M. globosa, Malassezia furfur and M. sympodialis have been most frequently isolated from seborrheic dermatitis patients [32, 33]. Concerning AEDS there are contradictory reports; in a Japanese study [32] M. furfur was the most common species cultured, whereas nested PCR used in another study from Japan showed that M. globosa and M. restricta could be detected on the skin in 90% of the AEDS patients, and M. sympodialis and M. furfur on 40% of the patients [34]. In studies from Canada, Russia and Sweden, M. sympodialis was reported as the most frequent species in both AEDS patients and healthy individuals [33, 35, 36].…”
Section: Malasseziamentioning
confidence: 99%
“…M. globosa, Malassezia furfur and M. sympodialis have been most frequently isolated from seborrheic dermatitis patients [32, 33]. Concerning AEDS there are contradictory reports; in a Japanese study [32] M. furfur was the most common species cultured, whereas nested PCR used in another study from Japan showed that M. globosa and M. restricta could be detected on the skin in 90% of the AEDS patients, and M. sympodialis and M. furfur on 40% of the patients [34]. In studies from Canada, Russia and Sweden, M. sympodialis was reported as the most frequent species in both AEDS patients and healthy individuals [33, 35, 36].…”
Section: Malasseziamentioning
confidence: 99%
“…The taxonomy of genus Malassezia was revised in 1996 [12], and further new species have been reported in recent years [15,16,17,18,19]. There have been several studies concerning the frequency of isolation of each species and its correlation with the clinical manifestations of AD [20,21,22,23,24,25]. These previous studies used either nonculture or culture methods, and the differences by gender and body part of Malassezia species isolated from AD patients have not been thoroughly considered.…”
Section: Introductionmentioning
confidence: 99%
“…The first set of primers used were Trichosporongenus specific primers (TRF -5'AGAGCCTACCATGGTATCA 3' TRR-5'TAAGACCCAATAGAGCCCTA3') [19]. They would precisely amplify only Trichosporon species, by aligning with the small subunit (SSU) of ribosomal DNA (rDNA) sequences, since this region is not conserved in other medically important yeasts.…”
Section: Trichosporon Specific Pcrmentioning
confidence: 99%
“…PCR was performed with Trichosporon genus specific primers to double check for accurate identification of the genus [19]. This pair of primer is Trichosporon specific and amplified part of the nucleotide sequences of the rDNA small subunit (18S).…”
Section: Molecular Identificationmentioning
confidence: 99%
See 1 more Smart Citation